Role of the RAGE Axis during the Immune Response after Severe Trauma: A Prospective Pilot Study - Florian Uhle; Christoph Lichtenstern; Thorsten Brenner; Thomas Fleming; Christian Koch; Andreas Hecker; Christian Heiss; Peter Paul Nawroth; Stefan Hofer; Markus Alexander Weigand; Katja Weismüller (Mediators of Inflammation)
Background. Severe traumatization induces a complex pathophysiology, driven by the patient’s own immune system. The initial activation is a result of damage-associated molecular patterns, which are released from disrupted and dying cells and recognized by immune receptors, for example, RAGE. In this study we aimed to evaluate the contribution of the RAGE axis to early and late immune responses. Methods. We enrolled 16 patients with severe trauma together with 10 patients after major abdominal surgery and 10 healthy volunteers. Blood samples were taken on admission and every 48 h for a total of 8 days. Plasma concentrations of various RAGE ligands as well as RAGE isoforms and IL-6 were measured by ELISA. Monocyte surface expression of RAGE and HLA-DR was assessed by flow cytometry. Results. High and transient levels of IL-6 and methylglyoxal characterize the early immune response after trauma, whereas samples from later time points provide evidence for a secondary release of RAGE ligands. Conclusion. Our results provide evidence for a persisting activation of the RAGE axis while classical mediators like IL-6 disappear early. Considering the immunocompromised phenotype of the monocytes, the RAGE ligands might be substantial contributors to the well-known secondary stage of impaired immune responsiveness in trauma patients.